Real world population pharmacokinetic study in children and young adults with inflammatory bowel disease discovers novel blood and stool microbial predictors of vedolizumab clearance. Issue 5 (31st October 2022) - Colman, Ruben J.; Mizuno, Tomoyuki; Fukushima, Keizo; Haslam, David B.; Hyams, Jeffrey S.; Boyle, Brendan; Noe, Joshua D.; D'Haens, Geert R.; Van Limbergen, Johan; Chun, Kelly; Yang, Jane; Denson, Lee A.; et al.
Summary: Background: Vedolizumab for inflammatory bowel disease (IBD) is often intensified based on distinct pharmacokinetics in children. Prior adult‐specific population pharmacokinetic models have identified limited covariates of drug clearance. Aims: To establish a population pharmacokinetic model for children and young adults to identify novel covariates of drug clearance to better account for paediatric‐specific inter‐patient variability in vedolizumab pharmacokinetics; a key secondary exploratory aim was to identify microbial signatures of pharmacokinetic outcomes in a subset of patients. Methods: The study included data from 463 observed vedolizumab concentrations (59 peaks and 404 troughs) from 74 patients with IBD (52 with Crohn's disease and 22 with ulcerative colitis or unclassified IBD, median age 16 years). Pharmacokinetic analysis was conducted with non‐linear mixed effects modelling. For the evaluation of the exposure–response relationship, clinical outcomes were evaluated by trough levels, clearance and vedolizumab exposure. Whole‐genome metagenomic sequencing was conducted at baseline and week 2. Results: A two‐compartment population pharmacokinetic model was identified with a clear correlation between CL and weight, erythrocyte sedimentation rate, and hypoalbuminemia. Trough concentrations before infusion 3 (37 μg/ml) and before infusion 4 (20 μg/ml) best predicted steroid‐free clinical remission at infusion 4. Using faecal metagenomics, we identified an early (baseline and week 2) abundance of butyrate‐producing species and pathways that were associated with an infusion 4 trough concentration >20 μg/ml. Conclusions: This novel paediatric vedolizumab pharmacokinetic model could inform precision dosing. While additional studies are needed, an abundance of faecal butyrate producers is associated with early response to vedolizumab, suggesting that microbial analysis may be beneficial to biological selection. Abstract : Population pharmacokinetic study to identify novel predictors (blood and stool) of vedolizumab clearance in children and young adults. Specifically, low serum albumin and elevated erythrocyte sedimentation rate (ESR) resulted in accelerated drug clearance. These data suggest that children may require more frequent vedolizumab infusions to achieve therapeutic drug targets.